Is the Portable Chest Radiographic More Reliable to Reveal Covid19 in Highly Suspicion Patient before Real-Time Reverse Transcription Polymerase Chain Reaction (RT-PCR) Test? - Albazi, Bushra A. A.; Albaz, Dr Noof.; Alqahtani, Dr Nayef.; Salih, Dr. Angham; Mohtasab, Dr Rafat (International Journal of Innovative Research in Medical Science, 2021)
A large number of patients with coronavirus disease 2019 (COVID-19) present at hospitals. There are a limited number of isolation rooms open, and patients must often wait a long time to get a reverse transcription-polymerase chain reaction (RT-PCR) test done. This necessitates the introduction of effective triage plans. A patient with suspicions is referred to an emergency room (ED) depending on their medical record for a simple physical assessment, blood test findings, and chest imaging.A retrospective study design was conduct at Prince Sultan Medical Military City (PSMMC). Ethical approval was obtained from the institutional board to wave the consent forms since it is a retrospective study. Only the primary investigator has had the data access to the patients’ medical records. The collected patient records were under specific categories, including symptoms score starts from 5 and above, RT-PCR test result done after CXRP imaging, the patient admitted to the emergency department (ED). Excluding all CXRP done after RT-PCR TEST, positive Covid 19 admitted to the intensive care unit (ICU), pediatric patients, and patients with score symptoms were less than five. Two experienced radiologists reviewed the images blindly, and the inter-observer reliability of observations noted by the radiologists was calculated. As for the relationship between the x-ray reading and the RT-PCR test result, our results showed a high correlation between the variables (chi-square χ² = 12.44, with df =1, and p<0.001). The sensitivity of x-ray diagnosing covid19 was 65.52 %, while the specificity was 54.51 %, and the accuracy of radiologists reading was 58.17 %. Furthermore, the positive predictive value (PPV) was 41.76 %, and the negative predictive value (NPV) was 76.05%. Finally, the false positive rate (type-i error (alpha) was 45.49%, and the false-negative rate (type-ii error (beta) was 34.48% Our research findings show that CXRP imaging can detect COVID-19 infection in symptomatic patients and can be a valuable addition to RT-PCR testing. In an inpatient ED environment where availability of test kits, laboratory equipment, and laboratory personnel is compromised and risks delaying patient treatment and hospital workflow, serial CXRP could theoretically be used as an adjunct diagnostic function and monitoring in patients suspected of having COVID-19.